Analisis Minyak Atsiri Daun Cengkeh (Syzygium aromaticum L.) Dari Tempat Tumbuh Dengan Ketinggian Yang Berbeda - Wijaya, Luh Gede Artha Saridewi; Arpiwi, Ni Luh; Astarini, Ida Ayu (Metamorfosa: Journal of Biological Sciences, 2022)
ABSTRACT A research was carried out to determine the yield, content of constituent compounds, and analysis of the quality of clove leaf essential oil ( Syzygium aromaticum L.) at different altitudes. The study used dry clove leaves obtained from Buleleng Regency, Bali Province with an altitude of 300 meters above sea level (masl), 600 masl, and 900 masl. Extraction of essential oils was carried out by steam distillation. The essential oil obtained was analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) and the quality was tested using the quality requirements of SNI 06-2387-2006. Parameters observed were yield, identification of constituent compounds, analysis of essential oil quality including color, odor, specific gravity, and refractive index, solubility in alcohol, optical rotation, total eugenol and caryophyllene. The results showed that clove leaf essential oil in the lowlands (300 masl) had a higher yield of 2.05% and more types of active compounds than in the optimal altitude (600 masl) which was 1.45% and the highlands (900 masl) was 1.85%. The main compounds that make up clove leaf essential oil were eugenol, caryophyllene, and humulene. Other compounds were longifoline, nootkatone, naphthalene, citronellal, and cyclohexene. The clove leaf essential oil from the three heights met the quality requirements of SNI 06-2387-2006. Keywords: Essential oil, cloves, eugenol, GC-MS, secondary metabolites